Comparison of Submillinewton Thrust Measurements Between a Laser Interferometer and a Load Cell on a Pendulum Balance - Tsifakis, Dimitrios; Charles, Christine; Boswell, Rod (Frontiers in Space Technologies, 2021)
Reliable measurements of thrust from systems to be flown on satellites are essential to ensure repeatable maneuvering capability of small nanosatellites. Thrusters can be used to vary spacecraft orientation, detumbling, and orbit change. Tests have been conducted in a low-pressure vacuum system using a cold gas prototype thruster and two independently calibrated methods: a four-point pendulum with a laser interferometer displacement sensor and a load cell, both of which have measurement capabilities from tens of micronewtons to tens of millinewtons. The agreement is very good, lending confidence in both methods. The advantages and disadvantages of both methods will be discussed. They include absolute accuracy, low thrust accuracy, temporal resolution, simplicity of operation, cost, and sensitivity to vibrations generated by laboratory equipment such as pumps, fans, bumps, and human movement.